Recombinant Human Thyrotropin-Aided Radioiodine Therapy in Tracheal Obstruction by an Invading Well-Differentiated Thyroid Carcinoma. (27th February 2013) - Pontikides, Nickolaos; Karras, Spyridon; Papagiannis, Antonios; Kaprara, Athina; Anagnostis, Panagiotis; Noussios, George; Doumas, Argyrios; Goropoulos, Apostolos; Iakovou, Ioannis; Kotronis, Georgios; Bantis, Konstantinos; Krassas, Gerasimos
Abstract : Papillary thyroid carcinomas (PTCs) usually extend to lymph nodes in the neck and mediastinum. Rarely, they invade the neighboring upper airway anatomical structures. We report a 56-year-old woman who presented with symptoms of upper airway obstruction. Imaging studies revealed a lesion derived from the thyroid which invaded and obstructed the trachea, which appeared to be a highly differentiated PTC. Total thyroidectomy was performed, with removal of the endotracheal part of the mass along with the corresponding anterior tracheal rings. Two months later, a whole body I 131 scan after recombinant human thyroid-stimulating hormone (rh-TSH) administration was performed and revealed a residual mass in upper left thyroid lobe. Subsequently, 150 mCi I 131 were given following rh-TSH administration. Nine months later, there was no sign of residual tumor. This case is the first one reported in the literature regarding rh-TSH administration prior to RAI ablation in a PTC obstructing the trachea.